Is an archaeon the ancestor of eukaryotes?. (12th January 2023) - Spang, Anja
Abstract: The origin of complex cellular life is a key puzzle in evolutionary research, which has broad implications for various neighbouring scientific disciplines. Naturally, views on this topic vary widely depending on the world view and context from which this topic is approached. In the following, I will share my perspective about our current scientific knowledge on the origin of eukaryotic cells, that is, eukaryogenesis, from a biological point of view focusing on the question as to whether an archaeon was the ancestor of eukaryotes.